Okak 1913, Eskimo tragen auf der Landungsbrücke für die Harmony bestimmte Lasten zu den Booten, an der Seite: Öl-und Forellenfässer - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of Inuit at Okak mission station in 1913 carrying loads along a jetty to the small boats that will deliver them to the "Harmony". The barrels on the side contain oil and fat. Photograph of Inuit at Okak mission station in 1913 carrying loads along a jetty to the small boats that will deliver them to the "Harmony". The barrels on the side contain oil and fat.